2015
DOI: 10.1177/1479972315619382
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in COPD patients

Abstract: Sexual dysfunction is a common problem in chronic obstructive pulmonary disease (COPD). We aimed to assess the presence of erectile dysfunction (ED) in COPD patients. Ninety-three outpatients who had been diagnosed as COPD and followed in Bolvadin State Hospital, Afyon, Turkey, were included in the study. All patients underwent pulmonary function tests and arterial blood gas analysis. They completed International Physical Activity Questionnaire (IPAQ), Medical Research Council (MRC) Dyspnea Scale, Short Form 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
3
18
0
4
Order By: Relevance
“…Studies evaluating sexual dysfunction before and after orthotopic liver transplantation (OLT) found controversial results and the prevalence seems to be similar to prior OLT . Arterial hypertension and diabetes have been previously associated with ED and also studies in other chronic disease such as chronic obstructive pulmonary disease found high prevalence rates . Depression and low HRQOL were associated with ED in chronic hepatitis C patients and we could show in our cohort that low libido, most likely owing to the burden of the disease, is significantly decreased in patients with ED.…”
Section: Discussionsupporting
confidence: 60%
“…Studies evaluating sexual dysfunction before and after orthotopic liver transplantation (OLT) found controversial results and the prevalence seems to be similar to prior OLT . Arterial hypertension and diabetes have been previously associated with ED and also studies in other chronic disease such as chronic obstructive pulmonary disease found high prevalence rates . Depression and low HRQOL were associated with ED in chronic hepatitis C patients and we could show in our cohort that low libido, most likely owing to the burden of the disease, is significantly decreased in patients with ED.…”
Section: Discussionsupporting
confidence: 60%
“…ED is associated with increased emergency and hospital admissions in patients with COPD. 29 Previous studies showed the association of ED with the risk and severity of COPD, 30 CAD, 31 and stroke. 32 A higher incidence of ER visits was observed in lung cancer patients with ED compared to those without ED in our study and we hypothesized that this may be due to the increased associated comorbidities including COPD, CAD, stroke and other diseases in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal of health management for patients with COPD is to improve their QoL, a major subjective marker of health status that is used to assess the effects of treatment and interventions [3, 6]. Men exhibit an increased prevalence of COPD after 60 years of age [7, 8], and sexual function is a QoL aspect that is markedly affected in men with COPD [9, 10]. The mechanism underlying sexual dysfunction in COPD patients is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these detrimental consequences, the effect of COPD on erectile function in men is underappreciated in clinical practice, partly because patients often feel uncomfortable talking about their erectile function with healthcare providers [7, 9, 10]. In Korea and other Asian countries, discussion of sexual issues is a cultural taboo: only 2% of men and women in Korea discuss their sexual health problems with medical personnel [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation